Financial Technology and the Legal Protection of Personal Data: The Case of Malaysia and Indonesia - Nurhasanah, Nurhasanah; Rahmatullah, Indra (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
The presence of digital technology brings significant changes in many aspects of human life, including the economy and financial services. The rapid development of financial technology (fintech) is being responded quickly by many countries including Indonesia and Malaysia. Not only conventional fintech, but Sharia fintech is also developing significantly in both countries. This phenomenon is caused by the efficiency and ease of fintech. However, fintech in Indonesia is not followed by a comprehensive protection of personal data. The absence of special regulation on the protection of personal data in Indonesia causes the data often be misused by certain parties such as being stolen, sold, transferred and eliminated irresponsibly causing harm to fintech users. Meanwhile, Malaysia has built a legal system of personal data protection since 2010 and becomes the first country in the ASEAN region to have a comprehensive personal data protection law system. Therefore, the article aims to overview and compare the personal data protection law in Malaysia especially in fintech. To answer the problem, this study uses a normative-empirical method with a comparative law approach. The result of this article shows that Indonesia should learn from Malaysia by doing benchmarking as an effort to establish a comprehensive regulation for protecting personal data. A comprehensive regulation and law enforcement on the protection of personal data are urgently needed in Indonesia to protect the rights of fintech users.